Pengaruh Pembelajaran Ethno-Deep Learning terhadap Literasi Budaya Siswa - Baiq Zulfah Purni Sari Ningrum; Agus Muliadi; Laras Firdaus; Sri Nopita Primawati (Biocaster : Jurnal Kajian Biologi, 2026)
Enhancing students' cultural literacy is crucial amidst the currents of globalization that are causing shifts in local cultural values. Conventional teaching methods are considered inadequate for meaningfully integrating local culture into the learning process. Therefore, instructional innovation is needed to combine local wisdom with a deep learning approach specifically, through "ethno-deep learning." This study aims to determine the impact of ethno-deep learning on students' cultural literacy. A quasi-experimental method with a post-test-only control group design was employed. The study population consisted of all Grade X students at SMA Islam Al Azhar NW Kayangan, North Lombok Regency, during the 2025/2026 academic year. A saturated sampling technique was used, meaning the entire population served as the sample; this comprised two classes: a treatment group of 20 students and a comparison group of 20 students. Data collection instruments included a cultural literacy questionnaire and an observation sheet to monitor the implementation of instruction. The data were analyzed using the Mann-Whitney U test to determine whether there was a significant difference in cultural literacy between the treatment and comparison groups. The analysis revealed significant differences between the groups across all dimensions of cultural literacy: understanding cultural complexity, knowledge of one's own culture, and cultural concern. This was evidenced by a Mann-Whitney U test significance value of 0.000 (Sig ≤ 0.1), leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1). The study concludes that ethno-deep learning significantly influences students' cultural literacy. This approach proved effective in enhancing students' understanding, awareness, and concern regarding culture through a learning process that is contextual, meaningful, and student-centered.